Methods for Providing Therapeutic Agents to Treat Damaged Spiral Ganglion Neurons - Bianchi, L. M.; Raz, Y. (Current Drug Targets-CNS & Neurological Disorders, 2004)
Sensorineural hearing loss, characterized by damage to sensory hair cells and / or associated nerve fibers is a leading cause of hearing disorders throughout the world. To date, treatment options are limited and there is no cure for damaged inner ear cells. Because the inner ear is a tiny organ housed in bone deep within the skull, access to the inner ear is limited, making delivery of therapeutic agents difficult. In recent years scientists have investigated a number of growth factors that have the potential to regulate survival or recovery of auditory neurons. Coinciding with the focus on molecules that may restore function are efforts to develop novel delivery methods. Researchers have been investigating the use of mini osmotic pumps, viral vectors and stem cells as a means of providing direct application of growth factors to the inner ear. This review summarizes recent findings regarding the molecules that may be useful for restoring damaged spiral ganglion neurons, as well as the advantages and disadvantages of various delivery systems.
Keywords: hearing loss